A Review: Corona Virus (SARS CoV-2) that causes COVID-19 - Abdulhadi Ali Albaser (Journal of Pure & Applied Sciences, 2020)
Coronaviruses are widespread zoontic viruses, they cause infection in human. Colds is the most common disease caused by these viruses. They also responsible for severe diseases such MERS and SARS. SARS-CoV-2 is the new member of these viruses. It causes human respiratory infections; the most important symptoms of this disease are fever, dry cough and shortness of breath. This may develop into other symptoms such as kidney failure. 80% of infections recover without the need for medical intervention. To date, it has been linked with the deaths of approximately 700,000 person worldwide, including 93 deaths in Libya General hygiene such as washing hands, taking a distance not less than a meter and covering the nose and mouth while coughing and sneezing are among the most important personal measures in reducing the spread of the disease and the occurrence of infection.